Errors in Using Prepositions: An Analysis on English Freshmen Majoring on Literature at Universitas Negeri Padang in Academic Year 2019 - Nentis Nentis; An Fauzia Rozani Syafei (Journal of English Language Teaching, 2020)
The research was aimed at analyzing the English department students errors in using prepositions. The subject of this research was the the freshmen of English Department majoring on literature in academic year 2019. Out of 103 students, 31% of them were choosen to be a sample by using simple random technique. The data had been gathered by using gap-filling test. The results of the data analysis show that from 1240 answers in the test, there were 796 errors made by the students. The errors included 184 (59%) errors prepositions of time, 213 (69%) errors in prepositions of place, 236 (76%) errors prepositions of direction/movement and 163 (52%) errors other kinds of prepositions. In addition, related to the cause of errors, it was the target language that mostly causes the students commit errors (intralingual errors). Based on the findings, it can be concluded that the freshmen of English students commit 64% total of errors in using prepositions and the errors itself mostly are due to the students’ lack ability in grammatical.